Engineering the Anatase-Rutile Phase Composition of TiO2 through H2O2 Addition and Its Photocatalytic Activity - Sri Wahyuni; Sri Kadarwati; M. Alauhdin; Addy Rachmat; Nuril Huda; Eka Siti Rinjani; Ridho Prasetyo (Science and Technology Indonesia, 2026)
The synthesis of mixed-phase anatase–rutile TiO₂ has been carried out to improve its light response and photocatalytic activity. The synthesis of mixed-phase TiO₂ was performed through a sol–gel method in an alkaline solution and followed by a hydrothermal process in an autoclave at a temperature of 150 °C for 3 h. A 60 mL of 0.5 M HNO₃ was then added into the TiO₂ precipitate, followed by the addition of various amounts (0 mL, 10 mL, and 20 mL) of 30% H₂O₂. The suspension was homogenized by sonication for 30 min to obtain an anatase–rutile mixed phase. The resulting mixed-phase TiO₂ was further labeled as A0, A1, and A2, respectively. The High-Score analysis showed that the phase composition of TiO₂ was 9.4% anatase and 90.6% rutile (A0); 17% anatase and 83% rutile (A1); and 49.6% anatase and 50.4% rutile (A2). The diffuse reflectance spectra showed a shift in the band gap energy from 3.17 eV (fully anatase TiO₂) to 2.75–2.86 eV in A0, A1, and A2 mixed-phase TiO₂. These results suggested that the photocatalytic activity of A1 and A2 mixed-phase TiO₂ would occur in the early visible-light region (λ > 400 nm). The photocatalytic examination of the mixed-phase TiO₂ under LED and UV irradiation resulted in a decrease in rhodamine-B (Rh-B) concentration of up to 92%. However, the photocatalytic activity of mixed-phase TiO₂ did not outperform that of fully anatase TiO₂, which achieved a 98% reduction in Rh-B concentration.